RSPO2 suppresses colorectal cancer metastasis by counteracting the Wnt5a/Fzd7-driven noncanonical Wnt pathway. (28th August 2017) - Dong, Xiaoming; Liao, Wanqin; Zhang, Li; Tu, Xi; Hu, Jin; Chen, Tianke; Dai, Xiaowei; Xiong, Yan; Liang, Weicheng; Ding, Chaodong; Liu, Rui; Dai, Juji; et al.
Abstract: R-spondins play critical roles in development, stem cell survival, and tumorigenicity by modulating Wnt/β-catenin signaling; however, the role of R-spondins in noncanonical Wnt signaling regulation remains largely unknown. We demonstrate here that R-spondin 2 (RSPO2) has an inhibitory effect on colorectal cancer (CRC) cell migration, invasion, and metastasis. Reduced RSPO2 expression was associated with tumor metastasis and poor survival in CRC patients. The metastasis-suppressive activity of RSPO2 was independent of the Wnt/β-catenin signaling pathway but dependent on the Fzd7-mediated noncanonical Wnt signaling pathway. The physical interaction of RSPO2 and Fzd7 increased the degradation of cell surface Fzd7 via ZNRF3-mediated ubiquitination, which led to the suppression of the downstream PKC/ERK signaling cascade. In late-stage metastatic cancer, Wnt5a promoted CRC cell migration by preventing degradation of Fzd7, and RSPO2 antagonized Wnt5a-driven noncanonical Wnt signaling activation and tumor cell migration by blocking the binding of Wnt5a to the Fzd7 receptor. Our study reveals a novel RSPO2/Wnt5a-competing noncanonical Wnt signaling mechanism that regulates cellular migration and invasion, and our data suggest that secreted RSPO2 protein could serve as a potential therapy for Wnt5a/Fzd7-driven aggressive CRC tumors. Highlights: The role of RSPO2 in CRC tumor metastasis was investigated. RSPO2 inhibits CRC metastasis through Fzd7-mediated noncanonical Wnt pathway. Wnt5a promotes CRC cell migration by preventing the degradation of Fzd7. RSPO2 competes with Wnt5a for binding to its receptor Fzd7. Reduced RSPO2 expression is associated with poor survival for CRC patients.